The Analysis Study of Management, Complication and Outcome after Thyroidectomy and Parathyroidectomy: A Comprehensive Systematic Review - Adinugroho, Prasetio; Randy, Randy (The International Journal of Medical Science and Health Research, 2024)
Backgrounds : Thyroid and parathyroid surgeries are essential in treating various endocrine disorders, including large symptomatic goiters, thyroid malignancies, and primary hyperparathyroidism (PHP). Thyroidectomy is widely performed for benign and malignant conditions, while parathyroidectomy is the only curative treatment for PHP. Objective : This systematic review aims to analyze the management strategies, complications, and outcomes associated with thyroid and parathyroid surgeries. It explores factors such as surgical approach, surgeon experience, and procedural complexity in influencing outcomes. Methods: The review evaluates recent advancements in minimally invasive techniques and enhanced recovery protocols by synthesizing existing literature on thyroidectomy and parathyroidectomy procedures. Results: The findings highlight the importance of comprehensive preoperative assessments, meticulous surgical techniques, and vigilant postoperative care to minimize complications such as hypocalcemia and RLN injury. Surgeon experience and individualized patient management were shown to significantly influence surgical outcomes. Conclusion: Future research should focus on developing standardized management protocols to optimize patient safety and recovery, especially in the evolving context of minimally invasive techniques.